2021
DOI: 10.1177/21925682211037265
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorder in Patients Undergoing Primary 1- to 2-Level Anterior Cervical Discectomy and Fusion Is Associated With Longer In-Hospital Lengths of Stay and Higher Rates of Readmissions, Complications, and Costs of Care

Abstract: Study Design: Retrospective study. Objective: To determine whether opioid use disorder (OUD) patients undergoing 1- to 2-level anterior cervical discectomy and fusion (1-2ACDF) have higher rates of: 1) in-hospital lengths of stay (LOS); 2) readmissions; 3) complications; and 4) costs. Methods: OUD patients undergoing primary 1-2ACDF were identified within the Medicare database and matched to a control cohort in a 1:5 ratio by age, sex, and medical comorbidities. The query yielded 80,683 patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Other studies reported similar findings concerning patients who were exposed to opioids before undergoing total shoulder arthroplasty 17 . It has also been demonstrated that opioids have a negative effect on the hospital course and complications after orthopaedic surgery 6,11,20-25 . Indeed, multiple investigations have shown that preoperative opioid use was associated with a greater risk of readmission and revision rates, thromboembolic complications, 90-day episode-of-care costs, length of stay, and emergency department visits.…”
Section: Effect Of Opioids On Orthopaedic Patientsmentioning
confidence: 99%
“…Other studies reported similar findings concerning patients who were exposed to opioids before undergoing total shoulder arthroplasty 17 . It has also been demonstrated that opioids have a negative effect on the hospital course and complications after orthopaedic surgery 6,11,20-25 . Indeed, multiple investigations have shown that preoperative opioid use was associated with a greater risk of readmission and revision rates, thromboembolic complications, 90-day episode-of-care costs, length of stay, and emergency department visits.…”
Section: Effect Of Opioids On Orthopaedic Patientsmentioning
confidence: 99%